Teacher’s Instructional Scaffolding in Teaching Speaking To Kampung Inggris Rafflessia Rejang Lebong Participants - Anita Anita (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
The study was intended to explore the experiences of the teachers in teaching speaking to non-English department students using instructional scaffolding. The instructional scaffolding was perceived to enhance students’ approximation to control spoken and written text. The data were gained from in-depth interviews with three teachers who teach non-English Department students who join in Kampung Inggris Rafflessia (KIR) Rejang Lebong Course. To address the goal, there were two research questions formulated in this study; 1) What do teachers think about teaching speaking using instructional scaffolding? and 2) How do teachers implement instructional scaffolding in speaking class? The 30-minute interview was conducted twice with open-ended questions. Then, the gathered data were analyzed qualitatively using phenomenological method. Teachers’ instructional scaffolding provided many chances for the students to be active in the learning process. By using the scaffolding, the teachers perceived that the learning process becomes more effective. The study also concludes by offering suggestions for improving the teaching method and identifying avenues for further research.